Hidden Attributes and the Display of Information in Multiobjective Analysis - Schilling, David A.; McGarity, Arthur; ReVelle, Charles (Management Science, 1982)
Quite often in the creation of analytic models for decision problems involving multiple objectives, some of the objectives are excluded. This can be due to their being consciously or unconsciously hidden by the decisionmaker or due to the lack of quantifiable performance measures. The normal procedure for evaluation of alternatives by the decisionmaker involves the presentation of their performance with respect to the stated criteria. When there are hidden objectives, however, the impact of the policies cannot be fully evaluated. Without the values of performance measures for all objectives for each of the alternatives, the decision-maker's choice among them rests on his preference weightings of the modelled objectives alone. To facilitate the decisionmaker's evaluation with respect to the hidden attributes, the presentation of alternatives should include values of the decision variables as well as quantified criteria. Several methods for displaying information from a multiobjective analysis in terms of both the objectives and decisions are presented and discussed. Examples are provided for problems having both discrete and continuous solution spaces.